214 OESOPHAGECTOMY POST INDUCTION THERAPY: COMPLETE PATHOLOGICAL RESPONDERS VERSUS OTHERS. (14th September 2020) - Pokharkar, H; Patil, A; Mistry, R; Choudhary, Y; Kaushik, T
Abstract:  : Induction therapy is reported to improve outcomes in patient with loco regionally advanced cancer of oesophagus; benefit is most in patient who respond to neoadjuvant therapy. This study compares outcomes between patients with complete pathological response (Group A) and others (Group B). Methods: This is a retrospective analysis of prospectively maintained database of 257 patients with cancer oesophagus undergoing surgery after neoadjuvant therapy between 2009 and 2019. Parameters analysed were stage at presentation, type of induction therapy, pTNM stage, pattern of failure and overall survival. Results: 209(81%) patients received chemotherapy alone and 48(19%) chemoradiation. 43(17%) patients had complete pathological response. Of the complete responders 21/209(10%) and 22/48(45.8%) patients had received chemotherapy alone and chemoradiation respectively. Majority of patients in both groups were T3/4 (Group A:93%, Group B:93.9%) and node positive (GroupA:81.4%, GroupB:85%). Median number of lymph nodal yield for Group A and Group B was 22 and 20 respectively. Three(7%) patients in Group A had local recurrence and 2(4.7%) had distant failure. The same for non responders was 34(15.9%) and 49(22.9%). The median survival for Group A is 7.03 years and Group B is 2.1 years. Conclusion: The overall median survival is significantly higher for complete pathological responder as compared to partial or non responders. Despite complete pathological response some patients will have recurrences. Chemoradiation is associated with higher complete pathological response compared to chemotherapy alone.